Heat flow characterization and baseline of sandstone using infra-red thermography - Ibrahim, Y. (American Institute of Physics Inc., 2016)
Infra-red thermography was applied to sandstone to characterize and obtain a baseline or a reference thermal image for sandstone. The sample was imaged at room temperature and then heated and imaged again at different time intervals. The thermal images and the optical gradient obtained were analyzed, calibrated, and equated to actual-temperature measured geothermal gradient under controlled heat flux. Heat flow propagation is not consistent in the first time intervals (below 25 minutes). However, after that, the difference in temperature in the distal part and the proximal parts to the heat source almost remained constant. In general, the heat flow could fit to a linear model that is directly proportional to time. The results can be useful when applied to borehole thermal imaging, as well as in thermal conductivity and geothermal gradient determination. Â© 2016 Author(s).